The Relationship between Caregiving Burden, Social Support, and Family Quality of Life of Post-Ischemic Stroke Patients at Hospital X - Herlina, Herlina (Journals of Ners Community, 2024)
Ischemic stroke poses a significant long-term care burden on families. The high burden of caregiving has the potential to reduce the quality of family life, while social support is thought to moderate this relationship. This study is needed to analyze the dynamics of these three variables at RSUD X. This study aims to analyze the relationship between the burden of caregiving, social support, and the family quality of life of patients after ischemic stroke, as well as to test the role of social support as a moderator. This quantitative study with a cross-sectional design involved 410 families (primary caregivers) of post-ischemic stroke patients who were selected through purposive sampling. Data were collected using the Zarit Burden Interview (ZBI), Medical Outcomes Study Social Support Survey (MOS-SSS), and Family Quality of Life Scale (FQOL) questionnaires. Data analysis used the Spearman Rank and Moderated Regression Analysis (MRA) tests. The results showed a very significant negative relationship between the burden of caregiving and family quality of life (ρ = -0.712; p = 0.000). Social support was shown to play a significant role as a moderator (β = 0.164; p=0.005), where the negative impact of caregiving burden on quality of life was weaker in families with high social support. It is concluded that the burden of caregiving is a strong predictor of a decrease in family quality of life, but this negative effect can be mitigated by adequate social support. The implications of the findings emphasize the importance of integrating caregiver burden screening and strengthening family and community-based social support systems into the nursing care planning of stroke patients.